Relationship Between the Lipid Accumulation Product Index and Arterial Stiffness in the Chinese Population With Hypertension: A Report From the China H-Type Hypertension Registry Study - Shi, Yumeng; Hu, Lihua; Li, Minghui; Zhou, Wei; Wang, Tao; Zhu, Lingjuan; Bao, Huihui; Li, Ping; Cheng, Xiaoshu (Frontiers in Cardiovascular Medicine, 2022)
Background: The lipid accumulation product (LAP) index, as a new index to predict CVD, has attracted the attention of many researchers. The relation of LAP index with brachial-ankle pulse wave velocity (baPWV) has been evaluated in several previous studies and yielded inconsistent results. The study aimed to investigate the association between the LAP index and arterial stiffness in the Chinese population with Hypertension. Methods: We conducted a cross-sectional analysis in 4926 Chinese population with Hypertension (aged 64.42±9.44 years). The LAP index was developed from population-based frequency plots of adult waist circumferences and circulating triglyceride concentrations according to men and women. Arterial stiffness was determined by measuring baPWV. Results: Multivariate linear regression analyses showed that the LAP index was independently and positively associated with baPWV (Beta coefficients (β), 24.10 cm/s (95% confidence interval [CI]: 5.72, 42.49 cm/s). Consistently, Multivariate logistic analyses showed a positive association between LAP index risk of elevated baPWV (>75th percentile) (odds ratio [OR], 1.19; 95% CI 1.01, 1.41). A restricted cubic spline showed that a significant linear association existed between the LAP index and baPWV. In different subgroups of DBP, there is interaction between LAP index and baPWV ( DBP<90, 90-99, ≥100mmHg; P-interaction=0.006). Conclusion: LAP is significantly positively associated with baPWV and elevated baPWV in Chinese hypertensive adults and especially among participants with DBP≤99mmHg.